REDUCING FISCAL RELIANCE ON OIL, COMPARING OIL AND NON-OIL CONTRIBUTIONS TO FEDERAL REVENUE - Ossai, Tobias Chukwudi; Musa, Ganaka Kubi (FUDMA Journal of Sciences, 2025)
Nigeria’s fiscal framework is heavily dependent on oil revenues, which, despite contributing over 50% of government income, are highly volatile and poorly aligned with economic growth, exposing the country to external shocks and fiscal instability. This study aims to assess the relative contributions of oil and non-oil revenues to federal income, identify the structural constraints limiting non-oil revenue growth, and propose policy measures to enhance fiscal resilience. Employing Vector Autoregressive (VAR), Vector Error Correction (VECM), and Autoregressive Distributed Lag (ARDL) models on data from 1983–2023, the study examines short-run and long-run dynamics, cointegration, and adjustment mechanisms among GDP, exchange rate, inflation, non-oil revenue, and oil revenue. Results indicate that while oil revenue dominates federal income, it exhibits negligible long-run impact on GDP, whereas non-oil revenue, though underdeveloped, demonstrates stronger growth potential and short-run significance for economic expansion. Diagnostic tests confirm model robustness with no serial correlation, heteroscedasticity, or structural instability. Based on these findings, the study recommends the establishment of a National Oil Revenue Stabilization Fund, targeted development of high-potential non-oil sectors such as cocoa and lithium, and enhanced subnational revenue mobilization through institutional reforms, creating a sustainable pathway toward fiscal stability and economic diversification in Nigeria.
Keywords: Oil dependence; Fiscal diversification; Non-oil revenue; Economic resilience